Multicriteria Tools for the Implementation of Historic Urban Landscape - Antonia Gravagnuolo; Luigi Fusco Girard (Kvalita Inovácia Prosperita, 2017)
Purpose: The aim of this paper is to provide an overview and critical outlook of current evaluation tools for the implementation of the UNESCO Historic Urban Landscape (HUL) approach, focusing on the need of multidimensional / multistakeholder evaluation and impact assessment to turn heritage / landscape into a driver of sustainable development.